Variations in chemical defences and patterns of natural enemy attack between native and introduced populations of fireweed (Senecio madagascariensis): Implications for biological control. (9th December 2021) - Egli, Daniella; Harvey, Kerinne J.; Moore, Ben D.; Mitchell, Christopher; Olckers, Terence
Abstract: Native to South Africa, fireweed ( Senecio madagascariensis Poiret; Asteraceae) is an annual or short‐lived perennial herb that is highly invasive in Australia, where it is a target for biological control. Preliminary research indicates that fireweed may be undergoing adaptive changes along its invasion gradient in Australia. Changes, such as a shift in plant chemical defence, may influence fireweed's interaction with specialist insect herbivores, and hence the efficacy of a biocontrol program. As the testing of biocontrol candidates is a rigorous and lengthy process, confirmation of fireweed's susceptibility to insect attack may assist in fast tracking candidate suitability, where changes in plant defensive chemistry are found. In a large experimental field study in fireweed's native range, we compared the susceptibility of Australian and South African populations to insect natural enemy attack (in terms of plant biomass, insect richness and composition). Simultaneously, we assessed the variation in plant pyrrolizidine alkaloid concentrations and composition to rationalise any differences in natural enemy attack between populations. We found no significant differences in plant biomass across fireweed populations, despite significantly higher alkaloid concentrations in Australian populations. The composition of the endophagous (specialist) insect herbivore assemblage was related to alkaloid composition, but there were only minor differences in the assemblage between Australian and South African fireweed populations. Moreover, we found no significant differences in the abundance, richness or Shannon diversity indices of endophagous or ectophagous (generalist) insect herbivores between Australian and South African fireweed populations. Our results suggest that despite variations in chemical defence, Australian fireweed populations displayed neither reduced nor increased susceptibility to specialist insect herbivore attack, supporting the notion that if host‐specific biocontrol agents are released, their impact in Australia is unlikely to be influenced by any changes in plant chemical defence.